2021
DOI: 10.3390/vaccines9060628
|View full text |Cite
|
Sign up to set email alerts
|

Interim Estimates of COVID-19 Vaccine Effectiveness in a Mass Vaccination Setting: Data from an Italian Province

Abstract: This retrospective cohort study compared the rates of virologically-confirmed SARS-CoV-2 infections, symptomatic or lethal COVID-19 among the residents of the Italian province of Pescara who received one or two doses of COVID-19 vaccines, versus the unvaccinated. The official data of the National Health System were used, and a total of 69,539 vaccinated adults were compared with 175,687 unvaccinated. Among the subjects who received at least one vaccine dose, 85 infections (0.12%), 18 severe and 3 lethal COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 39 publications
2
63
0
2
Order By: Relevance
“…In the sensitivity analyses, VE for SARS-CoV-2 infections, symptomatic COVID-19 and COVID-19-related death got relatively lower when omitting over a single dose group of Maria et al’s work [ 33 ]; when omitting ≥ 14 days after the first dose group and ≥ 14 days after the second dose group of Alejandro et al’s work [ 14 ], VE for SARS-CoV-2 infections, hospitalization, ICU admission and COVID-19-related death got relatively higher; and VE for all clinical status of COVID-19 became lower when omitting ≥ 14 days after the second dose group of Eric et al’s work [ 34 ]. Incidence rate of adverse events and severe adverse events got relatively higher when omitting China CDC’s data [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the sensitivity analyses, VE for SARS-CoV-2 infections, symptomatic COVID-19 and COVID-19-related death got relatively lower when omitting over a single dose group of Maria et al’s work [ 33 ]; when omitting ≥ 14 days after the first dose group and ≥ 14 days after the second dose group of Alejandro et al’s work [ 14 ], VE for SARS-CoV-2 infections, hospitalization, ICU admission and COVID-19-related death got relatively higher; and VE for all clinical status of COVID-19 became lower when omitting ≥ 14 days after the second dose group of Eric et al’s work [ 34 ]. Incidence rate of adverse events and severe adverse events got relatively higher when omitting China CDC’s data [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the quality assessment of all the included studies are shown in Supplementary Table S2. Before 1 July 2021, 24 of 39 studies were published in peer-reviewed journals [9,12,[15][16][17]19,22,24,25,[28][29][30][31]33,34,36,37,[40][41][42]45,47,48,50] while the remaining 15 studies were posted online as preprint articles [11,18,20,21,23,26,27,32,35,38,39,43,44,46,49]. The characteristics of the studies are shown in Supplementary Table S1, including the country, study design, types of vaccines, outcomes, and SARS-CoV-2 variants involved in the studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Two recent reports showed that the Pfizer-BioNTech or Moderna two-dose COVID-19 vaccine regimen had a 94-95% efficacy at preventing symptomatic SARS-CoV-2 infection [10,11]. Although vaccine is the best tool to control the COVID-19 pandemic, vaccine shortages occur in many countries [12][13][14] in 2021. Therefore, nonpharmacological public health measures, such as wearing a face mask, quarantine, isolation, social distancing, and community containment, are still important and effective ways to prevent and control the COVID-19 outbreak before adequate vaccine availability [9].…”
Section: Covid-19 Preventionmentioning
confidence: 99%